Linksys WRT54G ultimate hacking - Asadoorian, Paul (Syngress ;, 2007)
This book will teach the reader how to make the most of their WRT54G series hardware. These handy little inexpensive devices can be configured for a near endless amount of networking tasks. The reader will learn about the WRT54Gs hardware components, the different third-party firmware available and the differences between them, choosing the firmware that is right for you, and how to install different third-party firmware distributions. Never before has this hardware been documented in this amount of detail, which includes a wide-array of photographs and complete listing of all WRT54G models currently available, including the WRTSL54GS. Once this foundation is laid, the reader will learn how to implement functionality on the WRT54G for fun projects, penetration testing, various network tasks, wireless spectrum analysis, and more! This title features never before seen hacks using the WRT54G. For those who want to make the most out of their WRT54G you can learn how to port code and develop your own software for the OpenWRT operating system. *Never before seen and documented hacks, including wireless spectrum analysis *Most comprehensive source for documentation on how to take advantage of advanced features on the inexpensive wrt54g platform *Full coverage on embedded device development using the WRT54G and OpenWRT.
Print version record
Keywords: Routers (Computer networks); Wireless communication systems; Routeurs (Réseaux d'ordinateurs); Transmission sans fil; COMPUTERS; Networking; Network Protocols; Home computer networks